2006
DOI: 10.1093/jxb/erj203
|View full text |Cite
|
Sign up to set email alerts
|

In planta mobilization of mPing and its putative autonomous element Pong in rice by hydrostatic pressurization

Abstract: The miniature Ping (mPing) is a recently discovered endogenous miniature inverted repeat transposable element (MITE) in rice, which can be mobilized by tissue culture or irradiation. It is reported here that mPing, together with one of its putative transposase-encoding partners, Pong, was efficiently mobilized in somatic cells of intact rice plants of two distinct cultivars derived from germinating seeds subjected to high hydrostatic pressure, whereas the other autonomous element of mPing, Ping, remained stati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
41
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 42 publications
4
41
1
Order By: Relevance
“…mPing was identified as the first actively transposing MITE in any organism (84,103). mPing transposition has been observed in vivo in response to various stress conditions and correlated with the coactivation of Pong, a distantly related autonomous transposon of the PIF/Harbinger superfamily (84,116,172). Recently, it was also shown that Pong and Ping-encoded proteins are necessary and sufficient to mobilize mPing in transgenic Arabidopsis plants (198c).…”
Section: Mechanism and Consequences Of Mite Amplificationmentioning
confidence: 99%
“…mPing was identified as the first actively transposing MITE in any organism (84,103). mPing transposition has been observed in vivo in response to various stress conditions and correlated with the coactivation of Pong, a distantly related autonomous transposon of the PIF/Harbinger superfamily (84,116,172). Recently, it was also shown that Pong and Ping-encoded proteins are necessary and sufficient to mobilize mPing in transgenic Arabidopsis plants (198c).…”
Section: Mechanism and Consequences Of Mite Amplificationmentioning
confidence: 99%
“…Four prominent exceptions are marked in red predicted that the mPing family was active since it has many identical elements in rice genome (Jiang et al 2003). Their transposability was experimentally verified using long-term cell culture (Jiang et al 2003), anther culture (Kikuchi et al 2003), and hybridization (Shan et al 2005) and hydrostatic pressurization (Lin et al 2006). Recently, another MITE family (mGings) was found to actively transpose in rice seedlings and plantlets regenerated from anther-derived calli (Dong et al 2012).…”
Section: Currently Active Mitesmentioning
confidence: 99%
“…Some elements insert at random, some insert near genes, and some insert preferentially into centromeric or heterochromatic areas (Schnable et al, 2009). Transposition of mobile elements can be activated by mutagenesis (Anderson, 1948;McClintock, 1950;Gowda et al, 2011), transformation (Wu et al, 2009), tissue culture (Peschke et al, 1987;Hirochika et al, 1996;Jiang et al, 2003;Barret et al, 2006;Gowda et al, 2011;Smith et al, 2012), wide hybridization (Liu and Wendel, 2000;Wang et al, 2010;Zou et al, 2011), and stress (Lin et al, 2006;Gowda et al, 2011).…”
Section: Transposable Elements Play a Dominant Role In Altering Genomesmentioning
confidence: 99%